Evaluation and comparison of the apical seal obtained with Biodentine after conditioning of root end with three different solutions using ultraviolet-visible spectrophotometer: An in vitro study - Sethuparvathi Anitha; Liza George; Josey Mathew; Sinju Paul; Tom Varghese; R V Vineet (Wolters Kluwer Medknow Publications, 2021)
Aim: The aim of the study is to evaluate and compare the apical seal obtained with Biodentine after conditioning of root end with three different solutions (HEBP, chitosan, and ethylenediaminetetraacetic acid [EDTA]). Materials and Method: Forty-eight maxillary incisors were selected and decoronated. Instrumentation was done with protaper rotary files up to F4 file and obturated with AH plus sealer (Dentsply, Germany) and Protaper gutta-percha cone using lateral condensation technique. The apical part of each root was resected at 90° to the long axis of the root for 3 mm, and retrograde cavity preparation was done in standardized dimensions. The teeth were randomly divided into four groups with 12 samples in each group and later subjected to a standard regimen of 3 ml of respective solutions for 5 min: Group I - 18% HEBP, Group II - 0.2% chitosan, Group III - 17% EDTA, Group IV - saline (control). All teeth were then restored with Biodentine (Septodont, USA). Samples were coated with two coats of nail varnish except in the apical 3 mm which will be immersed in 5 ml of 2% methylene blue dye and stored in incubator for 72 h. The nail varnish will be removed later, and the teeth will be immersed in 35% nitric acid for 72 h. The solutions were then filtered using a fine-grit filter paper and centrifuged at 2000 rpm for 1 min. The solutions thus collected will be used to determine absorbency in ultraviolet-visible spectrophotometer. Results: The mean values of absorbance were greatest for Group IV (saline) followed by Group III (17% EDTA), Group II (0.2% chitosan), and Group I (18% HEBP). Group IV (saline) and Group III (17% EDTA) have got statistically significant difference with all the other groups. Group II has got statistically significant difference with all the other groups except Group I. Conclusion: Within the limitations of the study, it was concluded that irrigation with newer agents significantly influenced the sealing ability of biodentine. Root-end irrigation with 18% HEBP and 0.2% chitosan showed the least microleakage when compared to 17% EDTA.